INFORMATION MATHEMATICALl ALGORITHM VERIFICATION PRIMARY AND SECONDARY TUBERCULOSIS - Ільницький, Г. І. (Science-based technologies, 2016)
Based on the mathematical principles of information and digital technologies carried out assessment of clinical and radiological and laboratory manifestations of tuberculosis inflammation. Established performance criteria diagnostic process, based on the proposed parameters. Standing algorithm for diagnosis of pulmonary tuberculosis in 76 patients and 81 primary - secondary tuberculosis informatsinoho bank using clinical and laboratory data, thus improving the quality of verification disease to 90.7% and 85.2% respectively. The aim of the study was to improve the efficiency of diagnosis of pulmonary tuberculosis by mathematical modeling of the most informative clinical symptoms and laboratory parameters of disease, given the nature of specific inflammation. Formed the basis of the research results of clinical and laboratory data 157 patients with pulmonary tuberculosis different origin, interpreted using mathematical modeling technology. The results showed that the correct diagnosis was identified in 69 of 76 patients in 69 primary and 81 - at secondary tuberculosis. The proposed algorithm verification in most observations allowed to determine the specific nature of the development process even in the case when the clinical and radiological manifestations resembling primary tuberculosis secondary .. Thus, mathematical modeling of diagnostic process helps to determine the most informative criteria of the disease and increase the effectiveness of verification TB to 90.7% and 85.2% respectively primary ivtorynnoho origin.